1991
DOI: 10.1177/00220345910700110901
|View full text |Cite
|
Sign up to set email alerts
|

Remineralization and Demineralization in situ from a Triclosan/Co-polymer/Fluoride Dentifrice

Abstract: An in situ study was conducted to evaluate the effect of a dentifrice containing 1100 ppm F (NaF) and triclosan, an anti-plaque agent, on remineralization of artificially-formed caries lesions in thin sections of human enamel. The thin sections were placed in mandibular partial dentures of 15 subjects and covered with a steel mesh to provide an area for plaque accumulation. The subjects brushed their teeth and dentures three times daily for two-week periods in a cross-over design, after which the specimens wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

1992
1992
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…However, it is believed that the FabV type enoyl acyl reductase carrier protein, which is also an isoenzyme present in the cell membrane of P. aeruginosa, confers resistance to TCS 20 . Thus, TCS can possibly be indicated for patients at high risk for caries due to its antimicrobial action against S. mutans observed in this study and its effectiveness as an adjuvant to fluoride and remineralization capacity already reported 14 . Although studies observed a decrease in dental plaque using toothpaste with triclosan 9,11,12 , no study has compared the caries incidence of patients using TCS with other agents.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…However, it is believed that the FabV type enoyl acyl reductase carrier protein, which is also an isoenzyme present in the cell membrane of P. aeruginosa, confers resistance to TCS 20 . Thus, TCS can possibly be indicated for patients at high risk for caries due to its antimicrobial action against S. mutans observed in this study and its effectiveness as an adjuvant to fluoride and remineralization capacity already reported 14 . Although studies observed a decrease in dental plaque using toothpaste with triclosan 9,11,12 , no study has compared the caries incidence of patients using TCS with other agents.…”
Section: Discussionmentioning
confidence: 58%
“…In this context, TCS has been employed as an adjunct to fluoride. A study indicated that a dentifrice containing 0.3% of TCS was highly effective in preventing and enhancing demineralization compared to a positive control sodium fluoride dentifrice 14 .…”
Section: Introductionmentioning
confidence: 99%
“…Since many dental products contain fluoride, it was also important to investigate the compatibility of fluoride with AA and triclosan. A study by Mellberg et al [ 84 ] showed that triclosan does not interfere with fluoride-mediated remineralization, which is essential for the caries-inhibiting effect of fluoride. We observed here that fluoride enhanced the anti-bacterial effect of both AA ( Figure 3 A) and triclosan ( Figure 3 B), with improved anti-bacterial activity of the triple treatment ( Figure 3 C).…”
Section: Discussionmentioning
confidence: 99%
“…[1,2]. Себебі тіс жарудан кейін бірден тістің қатты тіндері толығымен минералданбайды, эмаль кеңейтілген призмааралық кеңістіктермен сипатталады, олар "піскен" тістерге қарағанда 2,0-2,5 есе үлкен, тіс сұйықтығының микроциркуляторлық негізгі көлемі ұлғаяды және дентинде гипоминерализация аймақтары көрінеді [3][4][5]. Көбінесе жағдайды нашарлатады ауыз қуысының гигиенасы және мінез-құлық пен тамақтану режимінің бұзылуы (жас балаларда бұл бір жылдан кейін, әсіресе түнде, бөтелкедегі тәттілендірілген сұйықтықтармен немесе емшек сүтімен емізу; егде жастағы балаларда-тәттілерді жиі қолдану) [6].…”
unclassified